DAMPAK MIGRASI SIRKULER TERHADAP DESA ASAL MIGRAN - Sunarto Hs (Populasi, 1991)
This researchwas conductedvin two villages at Gunung Kidul Regency. The aim was to identify the complexity of circular migrations and their remittances such as migrants self-esteem, reason for migration, selection of places of destination, economic activity and their earnings, remittances, and the impacts of remittances on their places of origin. The findings of this research: all remittances (money, goods, knowledge, experience, skills, and ideas) had positive impacts on the village environment and incultivatingland. The village society had a positive perceptionon the circular migration, which eventually had been internalized.